EU-Turkey economic relations in the era of geo-economic fragmentation - Kadri Tastan (Stiftung Wissenschaft und Politik (SWP), 2024)
The foundation of the European Union-Turkey economic and trade relations lies in the Customs Union and more broadly in the bilateral preferential trade framework, established in December 1995. For over nearly three decades, this partnership has played a pivotal role in integrating Turkish industries into European supply chains, significantly multiplying bilateral trade volumes. However, as the global economic and geopolitical environment has changed and concerns about trade resilience and national security have increased, new trends such as protectionism, offshoring, or friend-shoring are increasingly being discussed. These global developments present new challenges but also opportunities for EU-Turkey relations.
Keywords: 320; Customs Union; single market; European Economic Area; deglobalisation; decarbonisation; re-shoring; friend-shoring; European Chips Act; Critical Raw Materials Act; Carbon Border Adjustment Mechanism; CBAM; Inflation Reduction Act; IRA; Green Deal